LIS Students' Diploma Theses as Digital Documents : Citation Analysis - Hebrang Grgić, Ivana (Array, 2014)
The purpose of the survey is to obtain results that would show citation patterns among Library and Information Science (LIS) students at the Department of Information and Communication Sciences, Faculty of Humanities and Social Sciences, University of Zagreb. Results will help Faculty library to evaluate its acquisition policy and to harmonize it with the students’ needs. Sources for the survey are diploma theses written by LIS students in 2011 that were deposited in institutional repository of the Faculty until the end of June 2012. The study is based on reference analysis. Results show that the majority of cites is to printed sources (78.5%). Most cited resource type is book, followed by journal articles. Half of the references are less than ten years old. Authorship is analysed as well – out of the total of 681 authors, about two thirds are Croatian authors. The most cited authors and source types are identified. Results show that students are familiar with using sources in English and are aware of the importance of different source types. Analysis gives the insight of the students’ citing practice and could be useful for the Faculty library, for students and also for educators and mentors in guiding their students.